ANATOMICAL STUDY OF THE MODERATOR BAND - Y., Raghavendra A.; Kavitha; Kumar, Arunachalam; Tarvadi, Pratik; R., Harsha C. (Journal of Health and Allied Sciences NU, 2013)
Moderator band is a muscular trabecula which extends from interventricular septal wall to the base of anterior papillary muscle in right ventricle of heart. This study was conducted on 20 hearts from adult human cadavers. Out of 20 specimens of heart we could observe the presence of moderator band in 17 and in rest 3 it was not visible for record. Origin length, thickness and distance from tricuspid valve were noted. The average length of the moderator band was 13.82cm with the SD of 3.94 and the average thickness being 4.46cm with the SD of 1.36. The average distance from tricuspid valve was 3.6cm with the SD of 1.01. As the moderator bands, or other large trabeculations, can be major obstacle for the repair of apical ventricular septal defects, the morphometric study of moderator band may help the surgeons during surgical procedures conducted for correction of such defects.
Keywords: Moderator band; ventricular septal defects; septomarginal trabecula; morphometry